DEVELOPMENT OF E-JOBSHEET DESTRUCTIVE TEST TO IMPROVE MATERIAL TESTING PROBLEM SOLVING CAPABILITY - Rochmad Novian Inderanata (Jurnal Pendidikan Teknik Mesin, 2024)
This research aims to determine: (1) the feasibility of e-jobsheet destructive tests according to material and media experts; (2) user response to the practicality of e-jobsheet destructive tests; and (3) the effectiveness of e-jobsheet destructive tests to improve material testing problem solving abilities. The research method uses research and development with a 4D model. Data collection techniques used interviews and questionnaires. Data were analyzed using quantitative descriptive. The research subjects were students of the Mechanical Engineering Vocational Education Study Program in the material testing course. The product specifications developed include: (1) introduction and use of SolidWorks software features; (2) tools & materials; (3) work steps; (4) working drawings; and (5) assessment criteria. The results of research and development show that: (1) e-jobsheets are declared very feasible by material and media experts; (2) the e-jobsheet is stated as practical by the user; (3) e-jobsheets are stated to have high effectiveness. It can be concluded that the destructive test e-jobsheet developed can be said to be suitable for use as digital teaching material for material testing courses.